FASHION FOR READING AND ITS FEATURES - Abdulazizov Abdulvahid Habibullaevich (Web of Journals Publishing, 2025)
It is known that a person strives for novelty in all aspects of his life. A person tries not to lag behind his contemporaries. This article presents some of the author's thoughts on fashion and its importance in reading culture.
Keywords: Reading culture, fashion, socio-philosophical and psychological mechanisms, material well-being, the desire to immerse oneself in the environment of the upper layers of society.